(untitled) (E Conference Zone, 2022)
This chapter provides a short introduction to the Voice over Long Term Evolution (VoLTE). According to 3GPP release 8 LTE was introduced providing higher access rates and lower latency, more efficient use of radio network resources which means lower cost per transmitted bit and voice spectral efficiency. Circuit switched domain was excluded and all applications – services are implemented as packet switched services. On 2009 the One Voice alternative was published by a number of communication service providers and vendors. The conclusion was that the IMS-based solution as defined by 3GPP was the best way to meet the end users’ expectations for service quality, availability, reliability when moving from existing circuit switched telephony services to IP-based LTE services. During 2010 the “One Voice” initiative was adopted by the Global System for Mobile Association (GSMA). That was supported by organizations, mobile service providers, vendors and handset manufacturers. The result of this action was a GSMA Voice over LTE (VoLTE) solution based on standards and supported by industry. Voice over LTE using IP based service poses several restrictions on Quality of Service, mainly over air interface. A general model approach is also presented in this chapter, contributing to the radio network designers planning algorithms and solutions.